Sex and APOE Genotype Alter the Basal and Induced Inflammatory States of Primary Astrocytes from Humanized Targeted Replacement Mice - Isha Mhatre-Winters; Aseel Eid; Yoonhee Han; Kim Tieu; Jason R. Richardson (ASN Neuro, 2023)
Apolipoprotein E4 (APOE4) genotype and sex are significant risk factors for Alzheimer's disease (AD), with females demonstrating increased risk modulated by APOE genotype. APOE is predominantly expressed in astrocytes, however, there is a lack of comprehensive assessments of sex differences in astrocytes stratified by APOE genotype. Here, we examined the response of mixed-sex and sex-specific neonatal APOE3 and APOE4 primary mouse astrocytes (PMA) to a cytokine mix of IL1b, TNFa, and IFNg. Pro-inflammatory and anti-inflammatory cytokine profiles were assessed by qRT-PCR and Meso Scale Discovery multiplex assay. Mixed-sex APOE4 PMA were found to have higher basal messenger RNA expression of several pro-inflammatory cytokines including Il6 , Tnfa , Il1b , Mcp1 , Mip1a , and Nos2 compared to APOE3 PMA, which was accompanied by increased levels of these secreted cytokines. In sex-specific cultures, basal expression of Il1b , Il6 , and Nos2 was 1.5 to 2.5 fold higher in APOE4 female PMA compared to APOE4 males, with both being higher than APOE3 PMA. Similar results were found for secreted levels of these cytokines. Together, these findings indicate that APOE4 genotype and female sex, contribute to a greater inflammatory response in primary astrocytes and these data may provide a framework for investigating the mechanisms contributing to genotype and sex differences in AD-related neuroinflammation.